2007
DOI: 10.5326/0430008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diazepam or Lidocaine Premedication on Propofol Induction and Cardiovascular Parameters in Dogs

Abstract: The effects of diazepam or lidocaine on the propofol induction dose and certain cardiovascular parameters were documented in this randomized, blinded study. Dogs received 0.9% saline (0.1 mL/kg intravenously [i.v.]), lidocaine (2 mg/kg i.v.), or diazepam (0.25 mg/kg i.v.) prior to propofol i.v. until loss of jaw tone was achieved (up to a maximum of 8 mg/kg). Propofol was followed by 0.3 mg/kg atracurium i.v. Direct arterial blood pressures and heart rates were recorded before premedication, induction, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
5
9
0
Order By: Relevance
“…Finally, the required dose of propofol was not significantly different (P=0.081) between the two groups. This latter observation is in agreement with the findings of Braun et al (), Kraus & Cazlan (), and Thompson & Rioja (). The lack of significant differences between groups may be related to the limitations of this study, which include the technique used for blood pressure monitoring, influence of premedication drugs, the sensitivity of the different scoring systems, the hand injection of propofol and the limited sample size.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Finally, the required dose of propofol was not significantly different (P=0.081) between the two groups. This latter observation is in agreement with the findings of Braun et al (), Kraus & Cazlan (), and Thompson & Rioja (). The lack of significant differences between groups may be related to the limitations of this study, which include the technique used for blood pressure monitoring, influence of premedication drugs, the sensitivity of the different scoring systems, the hand injection of propofol and the limited sample size.…”
Section: Discussionsupporting
confidence: 94%
“…In dogs undergoing craniectomy for tumour resection, mean arterial pressure (MAP) and HR did not increase significantly during endotracheal intubation after induction of anaesthesia with a combination of lidocaine (1 mg/kg) and propofol, but there was no control treatment (Raisis et al ). In healthy non‐premedicated dogs, the administration of diazepam (0.25 mg/kg) or lidocaine (2 mg/kg) IV, 2 minutes before induction of anaesthesia with propofol, did not reduce the propofol dose required for loss of jaw tone, but effects on endotracheal intubation were not reported (Braun et al , Minghella et al ). To the authors’ knowledge, only a few studies have compared the influence of lidocaine versus saline on adverse effects during endotracheal intubation in dogs (Jolliffe et al , Kraus & Cazlan , Thompson & Rioja ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported a dose-sparing effect of benzodiazepines on the propofol induction dose (Ko et al 2006). Propofol administered in an identical manner to that used in this study resulted in a dose of 4.8 mg kg )1 in dogs after diazepam 0.25 mg kg )1 (Braun et al 2007). Midazolam administered at a dose of 0.2 mg kg )1 intravenously 2 minutes prior to propofol induction over 60 seconds was found to induce acute behavioral changes (excitement) and decreased the dose of propofol (Stegmann & Bester 2001).…”
Section: Discussionmentioning
confidence: 91%
“…One report commented that no clinically significant changes in blood pressures or heart rates were observed when propofol was used in combination with diazepam [51]. In another study investigating the anesthetic cardiopulmonary effects of propofol in dogs premedicated with butorphanol, atropine and medetomidine, a transient decrease in blood pressure was noted after propofol injection [52].…”
Section: Discussionmentioning
confidence: 99%